Measuring business impact: the lessons from the business schools. Issue 2 (24th December 2020) - Kalika, Michel; Shenton, Gordon
Abstract : Purpose: The purpose of this paper is to present an example of a fully operational impact assessment system called Business School Impact System (BSIS). It is designed specifically for business schools with a particular emphasis on their local and regional impact. Since its creation, the process has been adapted to schools of engineering and indeed to entire universities. The question of its relevance to all organisations is on the table. Design/methodology/approach: Talking about measurement raises methodological issues that are common to all organisations. The methodology used in this chapter, particularly in its second part, is mainly inductive, based on direct experience in interviewing 44 business schools in 15 countries. The system was designed on the basis of a survey among around 20 actors of the education industries (deans, journalists). First of all, the system involves an extensive self-assessment phase based on the BSIS impact measurement framework consisting of 7 major impact dimensions and about 100 indicators. This is followed up by a two-day visit by two experienced experts (former deans) who engage in challenging discussions with internal practitioners and external stakeholders. Findings: The question of the relevance of the dimensions used by business schools for companies is systematically asked, and it is argued that the seven dimensions of impact can be applied to all organisations whatever their mission. Research limitations/implications: The methodology has not yet been tested on private organisations. Practical implications: The process can be easily adapted to companies and could permit them to assess in a shared framework their impact. So, the practical implications are potentially large. Social implications: One of the seven dimensions of impact is the social impact of the organisation and indeed the implications are significant in the social field. Originality/value: To the best of the authors' knowledge, the transfer of a process of impact measurement from the educational sector to companies is studied for the first time.